Iron from continental weathering dictated soft‐part preservation during the Early Ordovician. (1st December 2021) - Saleh, Farid; Lucas, Victoire; Pittet, Bernard; Lefebvre, Bertrand; Lalonde, Stefan V.; Sansjofre, Pierre
Abstract: The Fezouata Shale in Morocco is the most diverse Lower Ordovician unit yielding soft‐tissue preservation. Iron played a crucial role in the preservation of soft parts in this formation through the damage of bacterial membranes under oxic conditions and the pyritization of soft parts under the activity of bacterial sulphate reduction. However, the origin of Fe in this formation remains largely speculative. Herein, trace and rare earth elements were investigated in drilled‐core sediments from the Fezouata Shale. It is shown that a correlation exists between Fe and Al suggesting that most Fe has a detrital source. Elemental concentrations in the Fezouata Shale are most comparable to rivers and are the least similar to loess and sediments deposited near active island arcs. In this sense, continental weathering and its related Fe in river fluxes dictated occurrences of exceptional fossil preservation in the Fezouata Shale.